Reaching out - Mack, Katherine (Nat Rev Phys, 2020)
In the midst of the COVID-19 pandemic, science is crucial to inform public policy. At the same time, mistrust of scientists and misinformation about scientific facts are rampant. Six scientists, actively involved in outreach, reflect on how to build a better understanding and trust of science.